Applying Scenario Planning in the Future of Bank Oranye Priority Banking Services - Ratna Satutikirono; Yos Sunitiyoso (Journal of International Conference Proceedings, 2021)
Bank Oranye is engaged in the provision of priority banking services and becomes one of the leading Indonesia’s state-owned enterprises that provides global wealth management. Apparently, Bank Oranye faced an intense competition with several players in priority banking service (which gradually provides complete wealth management products and/or services and able to go digitalize) and compete with investment products substitute offered by Fintech. This research intends to uncover the possibilities by analyzing the driving forces that could affect the priority banking business. The end result is to develop the scenarios and the formulation of implications and options. The scenario planning is developed based on external analysis (using PESTEL model and Porter 5 Forces) and internal analysis (VRIO analysis and Business Model Canvas). The critical uncertainties are determined by conducting in-depth interviews with company’s experts and literature study. The two critical uncertainties that will affect priority banking business of Bank Oranye in the next 5 years are: Technology Development and Adoption in the core banking system (including the adoption among priority customers) and Government Policy and Regulations. These two critical uncertainties will shape the way Bank Oranye performs with its vision to becomes one stop financial solutions for its customers.